Pengaruh Internal Locus Of Control Dan Self Efficacy Terhadap Minat Menjadi Studentpreneur Di Indonesia - Wibowo, Wahyu Anggie; Dudija, Nidya (eProceedings of Management, 2024)
The number of unemployed in Indonesia has quite fantastic figures. This has an impact on economic instability.Steps in realizing entrepreneurial activities by the population can be started by providing provisions to the nation'snext generation so that their mentality becomes more mature entrepreneurs. The issue of this study is how muchinternal locus of control and self-efficacy influence the interest in becoming a studentpreneur in Indonesia.Meanwhile, the aim of this research is to find out how much influence internal locus of control and self-efficacy haveon interest in becoming a studentpreneur in Indonesia.The study method used in this study is a quantitative method. Data collection was gathered by distributingquestionnaires via social media. After that, data processing was carried out using Structural Equation Modeling(SEM). The results of this research show that the influence exerted by internal locus of control on over a desire to starta studentpreneur in Indonesia is relatively small, namely 9.4% and the influence exerted by studentpreneurs oninterest in becoming a studentpreneur is relatively large, namely reaching 100%. Then simultaneously the influenceexerted by internal locus of control and self-efficacy on over a desire to start a studentpreneur is also relativelylarge, namely 94.6%. Keywords-internal locus of control, self efficacy, studentpreneur, SEM